Diagnosis Accuracy of Carpal Tunnel Syndrome in Diabetic Neuropathy - Nicu Cătălin Drăghici (Medicina, 2020)
Background and objectives: Carpal tunnel syndrome (CTS) is a common pathology, but sometimes the diagnosis is delayed in patients with diabetic neuropathy (DN). The aim of the study is twofold: first, to compare the accuracy of ultrasound (US) with that of electroneurography (ENG) in the diagnosis of CTS associated with DN, using the clinical diagnosis as a reference standard, and second, to investigate the correlation between morphological US parameters and electrodiagnosis (EDX) measurements in patients with CTS and DN. Materials and Methods: This study included patients with DN. They were divided into two groups: Control (patients without CTS) and Cases (patients with CTS). We performed US and ENG in both hands, totaling 56 wrists, with 28 wrists in each group. Results: We found that the difference in the sensory distal latencies between the median and the ulnar nerves (ring finger) exhibited the highest diagnostic accuracy of all the US and ENG parameters, areas under the receiver operating characteristic (AUC) = 0.99 (95% CI 0.97–1), and it was significantly different from the best US diagnostic method. The wrist cross-sectional area (CSA) had the most accurate US diagnosis, while the wrist-to-forearm ratio had the worst AUC. Moreover, in the group of CTS and DN patients, the wrist CSA enlargement was statistically directly proportional to the median compound muscle action potential (CMAP) distal latency and inversely proportional to the antidromic median nerve conduction study (NCS) and the orthodromic median palm–wrist NCS. Conclusions: Both examinations can be used with confidence in the diagnosis of CTS overlapping with DN, but the EDX examination seems to be more accurate. Furthermore, we found a positive correlation between the US and EDX parameters.